Pricing Strategies of Organic Products in Surkhet Valley, Nepal - Rokaya, Ammar Bahadur; Pandey, Akhilesh Chandra (Journal of Nepalese Management and Research, 2023)
This study explores the pricing strategies of organic products in Surkhet Valley, Nepal. It seeks to examine how several factors, including production costs, market demand, competitor prices, distribution costs, and overall economic conditions, interact with one another. The study uses a quantitative methodology and includes 150 participants from the Surkhet Valley of Nepal, including farmers and organic products vendors. The study uses statistical tools to analyze the data gathered, concentrating on Smart PLS-4. The study finds that there is a strong relationship between important variables such as market demand, competitor prices, distribution costs, economic conditions, production costs and the price of organic products. The results highlight how important it is for companies to keep an eye on rival pricing strategies, minimize distribution expenses, and modify price strategies in reaction to shifting market dynamics. For businesses in Surkhet Valley, Nepal, to thrive sustainably, they must improve their comprehension of the factors that affect the price of organic products. The report emphasizes how crucial it is to keep production costs under control and match pricing policies to the demands of the market. It also emphasizes how important it is to monitor rival pricing, streamline distribution procedures, and maintain flexibility when modifying price tactics. Restrictions include the sample size and the exclusive focus on Surkhet Valley, which make it dangerous to extrapolate the findings to other settings. Still, the study provides a valuable starting point for businesses looking to expand sustainably in the organic product space.